Chinese herbal compound for multidrug-resistant or extensively drug-resistant bacterial pneumonia: a meta-analysis and trial sequential analysis with association rule mining to identify core herb combinations - Zhao, Shuman; Geng, Yanting; Shi, Jiaheng; Qian, Jing; Yang, Yebeilei; Dai, Dan; Yan, Zimin; Qi, Wensheng; Yu, Daxing; Zhao, Xin (Frontiers in Pharmacology, 2023)
Methods: Stata 16 and TSA 0.9.5.10 beta software were used for meta-analysis and trial sequential analysis (TSA), respectively, to explore the sources of heterogeneity. Results: Thirty-eight studies involving 2890 patients were included in the analyses. Meta-analysis indicated that CHC combined with antibiotics improved the response rate (RR = 1.24; 95% CI: 1.19–1.28; p < 0.0001) and microbiological eradication (RR = 1.42; 95% CI: 1.27–1.57; p < 0.0001); lowered the white blood cell count (MD = -2.09; 95% CI: -2.65 to -1.53; p < 0.0001), procalcitonin levels (MD = -0.49; 95% CI: -0.59 to -0.40; p < 0.0001), C-reactive protein levels (MD = -11.80; 95% CI: -15.22 to -8.39; p < 0.0001), clinical pulmonary infection score (CPIS) (MD = -1.97; 95% CI: -2.68 to -1.26; p < 0.0001), and acute physiology and chronic health evaluation (APACHE)-II score (MD = -4.08; 95% CI: -5.16 to -3.00; p < 0.0001); shortened the length of hospitalization (MD = -4.79; 95% CI: -6.18 to -3.40; p < 0.0001); and reduced the number of adverse events. TSA indicated that the response rate and microbiological eradication results were robust. Moreover, Scutellaria baicalensis Georgi, Fritillaria thunbergii Miq, Lonicera japonica Thunb, and Glycyrrhiza uralensis Fisch were identified as core CHC prescription herbs. Conclusion: Compared with antibiotic treatment, CHC + antibiotic treatment was superior in improving response rate, microbiological eradication, inflammatory response, CPIS, and APACHE-II score and shortening the length of hospitalization. Association rule analysis identified four core herbs as promising candidates for treating antibiotic-resistant bacterial pneumonia. However, large-scale clinical studies are still required.